1α,25(OH)2D3 and parathyroid hormone (PTH) signaling in rat intestinal cells: Activation of cytosolic PLA2 - Gentili, Claudia Rosana (2004)
In the current study, we have probed the role of cytosolic phospholipase A2 (cPLA2) activity in the cellular response to the calciotropic hormones, 1α,25,dihydroxy-vitamin D3 [1α,25(OH)2D 3] and PTH. Stimulation of rat enterocytes with either hormone, increased release of arachidonic acid (AA) [3H-AA] one-two fold in a concentration and time-dependent manner. The effect of either hormone on enterocytes was totally reduced by preincubation with the intracellular Ca 2+ chelator BAPTA-AM (5 μM), suggesting that the release of AA following cell exposure to the calciotropic hormones occurs mainly through a Ca2+-dependent mechanism involving activation of Ca 2+-dependent cPLA2. Calciotropic homone stimulation of rat intestinal cells increases cPLA2 phosphorylation (three to four fold). This effect was decreased by PD 98059 (20 μM), a MAP kinase inhibitor, indicating that this action is, in part, mediated through activation of the MAP kinases ERK 1 and ERK2. Enterocytes exposure to 1α,25(OH)2D3 (1 nM) or PTH (10 nM) also resulted in P-cPLA2 translocation from cytosol to nuclei and membrane fractions, where phospholipase subtrates reside. Collectively, these data suggest that PTH and 1α,25(OH)2D3 activate in duodenal cells, a Ca2+-dependent cytosolic PLA2 and attendant arachidonic acid release and that this activation requieres prior stimulation of intracellular ERK1/2. 1α,25(OH)2D3 and PTH modulation of cPLA2 activity may change membrane fluidity and permeability and thereby affecting intestinal cell membrane function.